Engineering and Economic Aspects of Soil and Water Conservation - Thiruvenkatasamy, K.R. (Journal of Soil and Water Conservation, 2022)
Soil Conservation measures vary front region to region depending upon the kind and intensity of problems, the soil and land characteristics and the rainfall pattern. In heavy rainfall areas, the problem is predominantly conservation of soils and therefore, structures are chosen to prevent the soil loss against onslaught of rainfall and consequent concentrated runoff In low rainfall areas, conservation of moisture becomes important. The runoff collected from the rainfall is transported safely to the valleys either through man made water-ways or natural drains without causing accelerated erosion. The unique problems of hilly areas require contour trenching, bench terracing and contour stone wall as some of the soil conservation structures. It is necessary to evaluate the efficacy of the structures and their economic viability. These aspects are discussed in the paper and substantiated by data generated at a Soil Conservation Research Institute, Uthagamanvalan.